Whole body vibration on offshore structures: an evaluation of existing guidelines for assessing low-frequency motions - Schwarzkopf, Marie-Antoinette; Scheu, Matti Niclas; Altay, Okyay; Kolios, Athanasios (International Society of Offshore and Polar Engineers, 2018)
An extensive literature research has been conducted to create an insight into the existing norms and standards regulating the assessment of human exposure to motions in offshore environments. A summary of current threshold values and their specific fields of application is included. The presented literature is analysed with respect to their applicability for assessing low frequency oscillatory motions of floating offshore wind turbines to which technicians are exposed during maintenance tasks. The review identifies the need for a consistent assessment method in combination with threshold values for floating structures.
Keywords: Floating offshore wind; motion sickness; human comfort; vibrations; whole-body-vibrations; motion criteria; Operation and maintenance